Myasthenia gravis unmasked by antipsychotic medication. Issue 1 (11th February 2013) - Wilson, Carol Lee; Ferguson, John
Abstract Several medications, including some antipsychotics, have been shown to worsen myasthenia gravis symptoms. Here, Drs Wilson and Ferguson report the case of a patient with bipolar affective disorder, whose undiagnosed myasthenia gravis was unmasked by antipsychotic medication used to treat a manic relapse and whose symptoms were first attributed to antipsychotic‐associated extrapyramidal sideeffects.